PENGEMBANGAN ALAT PERAGA KOTAK SIFAT CAHAYA SEBAGAI MEDIA PEMBELAJARAN IPAS SISWA SD - Malo, Ferdinanda Gole; Dinatha, Ngurah Mahendra; Dolo, Fransiskus Xaverius; Kua, Maria Yuliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to develop and test the validity and practicality of a light properties box as a learning media for students at UPTD SDI Ngoramawo. This teaching aid is designed to help students understand concepts of light properties, such as light traveling in straight lines, being reflected, refracted, and passing through transparent objects. The research uses a Research and Development (R&D) approach with a 3D development model (Define, Design, and Develop). The study was conducted at UPTD SDI Ngoramawo, Bajawa Subdistrict, Ngada Regency, East Nusa Tenggara Province, involving 5 fourth-grade students and 1 teacher. Data analysis was performed by subject matter experts, design experts, and language experts, all of whom are IPAS teachers. The data used includes quantitative data from expert validation results and responses from students and teachers through questionnaires, as well as qualitative data in the form of suggestions and feedback from the evaluators. The validation results showed a percentage of 90% from the subject matter expert, indicating that the teaching aid is considered highly valid for helping students understand the concepts being taught. This result shows that the teaching aid aligns with the learning objectives and can be easily understood by students. A score of 87% from the design expert reflects the evaluation of the visual and functional aspects of the teaching aid. With this value, the teaching aid is deemed to have a good and effective design in delivering the material, although there may still be small aspects that can be improved. The language expert gave a score of 82%. Teacher responses through the questionnaire reached 90.7%, while student responses reached 88%. The developed light properties box demonstrates high validity and practicality for use in IPAS learning in fourth-grade classrooms. The light properties box developed shows high validity with validation percentages of 90% from the subject matter expert, 87% from the design expert, and 82% from the language expert, indicating that the teaching aid aligns with the learning objectives, has an effective design, and uses clear, easily understandable language. Its practicality is confirmed through positive responses from teachers (90.7%) and students (88%), showing that the teaching aid is easy to use in daily learning and effective in helping students understand the concepts being taught